2019
DOI: 10.1177/2050157919843963
|View full text |Cite
|
Sign up to set email alerts
|

Making place with mobile media: Young people’s blurred place-making in regional Australia

Abstract: This paper investigates young people living in a regional Australian town and explores the ways that they negotiate place-making using mobile media. Australia has been characterised as a country of vast distances, and young people living in rural and regional areas are at the centre of narratives that position digital technologies as enablers or disruptors. This paper puts such deterministic discourses aside to focus on the ways place is made by young people living outside the city according to their own persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…One group links hybrid realities to placemaking such as virtual placemaking (Devine, 2017;Qabshoqa, 2018;Relph, 2007), radical placemaking (Gonsalves et al, 2021), hybrid placemaking (Bilandzic and Johnson, 2013), and smart placemaking (Najafi et al, 2021;Sepe, 2015), focusing on the creation of hybrid realities that could create a sense of immersion. The second group investigates social media use through mobile media in placemaking (Breek et al, 2018;Latorre, 2011;Polson, 2015;Waite, 2020).…”
Section: Theoretical Perspectives On Digital Placemakingmentioning
confidence: 99%
“…One group links hybrid realities to placemaking such as virtual placemaking (Devine, 2017;Qabshoqa, 2018;Relph, 2007), radical placemaking (Gonsalves et al, 2021), hybrid placemaking (Bilandzic and Johnson, 2013), and smart placemaking (Najafi et al, 2021;Sepe, 2015), focusing on the creation of hybrid realities that could create a sense of immersion. The second group investigates social media use through mobile media in placemaking (Breek et al, 2018;Latorre, 2011;Polson, 2015;Waite, 2020).…”
Section: Theoretical Perspectives On Digital Placemakingmentioning
confidence: 99%
“…But we may also expect them to be differently configured and to appear in new constellations of alignment vis‐à‐vis other rural performances. For a start, the everyday Internet has entailed a stretching of place (Waite 2020) and a renewed prominence of translocal relations (Greiner and Sakdapolrak 2013; Tenhunen 2011). Such elasticity is not entirely new but rather reflects a digital accentuation of long‐standing practices whereby social relations simultaneously stretch and compress our sense of geographical proximity, drawing distant places near while keeping others at a distance, notwithstanding the relative geographic location of those places.…”
Section: The Online Performance Of Rural Placesmentioning
confidence: 99%
“…In previous research, we have shown how social media technology has been folded into the pre‐existing technosocial configurations of rural places, where it intermingles with face‐to‐face encounters, mail‐delivered leaflets and weekly newspapers, physical posters at key meeting places, and other mundane technologies for rural sociability (Johansen and Fisker 2020). These findings have to be considered alongside related research at the intersection of social media and rural place, shedding new light on the relation between social cohesion and social media use in villages (Wallace et al 2017); online building and maintenance of social capital in rural communities (Tiwari, Lane, and Alam 2019); rural politics conducted through social media (Golding and Brannon 2020; Lundgren and Johansson 2017; Lundgren and Liliequist 2020); digitally extended place‐making by rural youth (Waite 2020; Waite and Bourke 2015); the use of social media and digital environments among LGBTQ people in rural areas (Liliequist 2020); online representations of the countryside in the tourism industry (Zhou 2014); and the mediatization of the rural‐urban divide (Jansson 2013; Jansson and Andersson 2012). In this paper, we seek to complement this growing body of knowledge by studying the role of place‐based Facebook groups in rural dwellers' outdoor activities and their engagement with local natures and landscapes, which make up a key part of their everyday life.…”
Section: Introductionmentioning
confidence: 99%
“…Theories concerning place-making [17,27,28] have highlighted how "place" is constructed and reconstructed through discursive processes. Specifically in relation to young people, Waite [27] considers the relevance of being attentive to how they produce regional places but also the combination in those processes of the construction of global flows, mobilities that influence social practices, and individuals' relationships with place.…”
Section: Theoretical Backgroundmentioning
confidence: 99%